IMPACTS OF SPORTS-SPECIFIC DRILLS ON SKILL PERFORMANCE VARIABLES AMONG MALE COLLEGE-LEVEL HANDBALL PLAYERS (A PILOT STUDY) - K.Ooraniyan; Dr. K. Murugavel (EPRA International Journal of Research and Development (IJRD), 2023)
Handball represents a unique combination of three fundamental athletic disciplines: running, jumping, and throwing. A training program known as sports-specific drills has been designed specifically to enhance athletic performance by targeting skill proficiency. These drills focus on improving game-specific abilities such as throwing accuracy, shooting precision, passing proficiency, as well as overall attributes including speed, power, endurance, flexibility, mobility, and agility. The primary objective of this study was to investigate the impact of sports-specific drills on skill performance variables among male college-level handball players. To accomplish this goal, a sample of five male handball players from CMS college of arts and science in Coimbatore district, aged between 18 and 25 years, was randomly selected. The study adopted a single-group design, where all participants underwent assessment using standardized tests for various skill performance variables. Throwing ability was evaluated using the 9-meter front throw test, shooting accuracy was measured using the one-armed throw test, and passing proficiency was assessed through the overhead pass test. The experimental group, consisting of the five participants, underwent a four-week period of sports-specific drills as part of a pilot study. The results of the study indicated a significant difference in the criterion variables. This difference was attributed to the implementation of sports-specific drills, which led to notable improvements in the throwing ability, shooting accuracy, and passing skills of the male college-level handball players. In summary, the study highlighted the effectiveness of sports-specific drills in enhancing skill performance variables among male college-level handball players. The findings suggest that the targeted training regimen positively influenced throwing ability, shooting accuracy, and passing skills. These results underscore the potential of sports-specific drills to enhance overall performance in handball by improving specific game-related skills.